(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2019)
This essay whose title has been called: In the thought of Elizalde: Discovering the deep structures of capitalism, aims to be a reflection and a critique on the construction of a new culture based on a model of consumption, which induces human beings to perform this practice without the minimum questioning about what they do and about the harmful effects they cause to nature and to themselves. Sustainability finds an obstacle in the economic system of capitalist production, because any economic practice that includes the sustainable as a transversal axis constitutes the antithesis of the system. In this essay, it is proposed to show traditional ways of living, such as that of indigenous peoples, ethnic communities and peasant communities, applying life strategies that incorporate sustainability. I invite the reader to follow the lines of this reflection and criticism of the essay entitled: What development can be called sustainable in the 21st century? The question of limits and Human needs.